Uncertainty, perception and the Internet - Maria Elena Bontempi; Michele Frigeri; Roberto Golinelli; Matteo Squadrani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2019)
Macroeconomic uncertainty consists of three components: the unobservable, the heterogeneous and the "uncertain". We are unaware of exactly when economic agents perceive uncertainty and which type of uncertainty interests them. This paper introduces and outlines a way of conducting large-scale data searches on the Web. We create the EURQ index of "economic uncertainty related queries" for both the USA and Italy. We show that the EURQ encapsulates agents' need to gather more information during periods of uncertainty. This need either spontaneously arises in the case of macro-real and political uncertainty, or is induced by the media in the case of normative and financial uncertainty. This distinction is extremely important when trying to understand the immediate impact of fiscal policy uncertainty on economic variables, and how financial shocks can produce a significant short-term impact on economic activity. It is also helpful when trying to solve the identification and endogeneity issues encountered in the literature when assessing the role of uncertainty.
Keywords: D80; D91; E66; C32; H30; 330; macroeconomic uncertainty measurement; perception of uncertainty; Internet searches; GoogleTrends; finance-based indexes; survey-based indexes; news-based indexes